Samsung’s Finances Shape Its Tech Future - Sarjono, Haryadi; Ravelliyo , Juvenn Elkins; Rainer , R.; Soeratin, Boyke Setiawan (Manunggal Halim Jaya, 2025)
Samsung Electronics has long captivated the world, not just with its cutting-edge gadgets and futuristic innovations but with a financial strategy that cements its dominance in the tech industry. This abstract explores the intricate relationship between Samsung's financial performance and its relentless pursuit of innovation, revealing the strategic elements that have propelled it to the pinnacle of the global tech ecosystem. Beyond its dazzling screens and advanced functionalities lies a well-orchestrated financial framework that fuels its success. This study uncovers the key factors behind its sustained growth by analyzing Samsung's revenue streams, market share dominance, strategic investments, and past financial milestones. Through an in-depth examination of financial reports, industry trends, and expert insights, we dissect the mechanisms that have shaped Samsung's trajectory in an ever-evolving technological landscape. More than just a case study, this analysis offers a blueprint for future tech giants, highlighting the crucial interplay between financial acumen, innovation, and strategic foresight. As we explore Samsung's ambitious vision for the future, we gain deeper insights into how financial strength is the bedrock for groundbreaking advancements, setting the stage for the next chapter in technological evolution.